Investigating Impact of Gasket Cylinder Addition and Octane Rating on Engine Performance - Bahtiar Rahmat; Mohammad Burhan Rubai Wijaya; Yuris Bahadur Wirawan; Fahmy Zuhda Bahtiar; Katiko Imamul Muttaqin (Universitas Muhammadiyah Yogyakarta, 2024)
The increase in people's mobility were reflected in the growing sales of motor vehicles. This has driven automotive manufacturers to compete in creating more powerful and efficient engines. These engines were designed with high compression ratios to achieve greater efficiency. High compression ratio engine re-quired fuel with the appropriate octane number to attain opti-mal performance. It is regrettable that many users had not un-derstood that an engine with high compression had required gasoline with a high octane rating as well. This research aims to investigate the impact of different compression ratios on the output power and torque of a single-cylinder combustion en-gine using RON 92, RON 95, and RON 100 gasoline. To modify the compression ratio, various numbers of gaskets were used on the cylinder head, with 2 and 3 gaskets for each configuration. A dynamometer test was employed to measure the differences in engine performance. The research results indicate that the engine with the highest compression pressure (11 Kg/cm2) using RON 100 gasoline produced the highest power of 7.90 kW, with the highest torque of 9.60 Nm. Conversely, the engine with the lowest compression pressure (10 Kg/cm2) using RON 92 gasoline produced the lowest power and the lowest torque.